Affica's Business Revolution: How to Succeed in the Wold's next Big Growth Market - Leke, Acha (Harvard Business Review Press, 2018)
Africa's Business Revolution provides the inside story on business in Africa and its future growth prospects and helps executives understand and seize the opportunities for building profitable, sustainable enterprises. From senior leaders in McKinsey's African offices and a leading executive on the continent, this book draws on in-depth proprietary research by the McKinsey Global Institute as well as McKinsey's extensive experience advising corporate and government leaders across Africa. Brimming with company case studies and exclusive interviews with some of Africa's most prominent executives, this book comes to life with the vibrant stories of those who have navigated the many twists and turns on the road to building successful businesses on the continent. Combining an unrivalled fact base with expert advice on shaping and executing an Africa growth strategy, this book is required reading for global business executives looking to expand their existing operations in Africa--and for those seeking a road map to access this vast, untapped market for the first time.